Fetopelvic disproportion in a hospital in Lima: prevalence, consequences, prediction and prevention - Pacora, Percy (2015)
OBJECTIVE. To ascertain the maternal and fetal variables that predict fetopelvic disproportion (FPD). SETTING. Hospital Nacional Docente Madre-Niño San Bartolome, Lima, Peru. DESIGN. Clinical retrospective study. Participants. Pregnant women with labor second stage arrest and birth by cesarean section. INTERVENTIONS. Retrospective study of our Perinatal Data Base from January 1, 1991 to December 31, 1999. Fetopelvic disproportion (FPD) was defined as labor arrest during 2 hours in nulliparous and 1 hour in multiparous women at the second stage of labor and delivery of the baby was by cesarean section. Logistic regression (LR) and ROC analysis were performed. MAIN OUTCOME MEASURES. FPD prevalence and associated conditions. RESULTS. The prevalence of FPD was 1,28% (583/45,386). As compared with women without FPD, women with FPD significantly presented lower stature –less than 160 cm–, were nulliparous, presented lower than 50 kg pregestational weight, developed preeclampsia, eclampsia, urinary tract infection, had in-hospital antenatal admission long before delivery and maternal death (p < 0,01). As compared to neonates without FPD, neonates with FPD presented cephalic diameter greater than 34 cm, PROM, neonatal resuscitation, 1 minute and 5 minute-Apgar score lower than 7, respiratory distress syndrome, perinatal asphyxia, sepsis, hyperbilirubinemia, admission to NICU and were LGA-infant (p < 0,01). The formula to establish FPD in Peruvian population was: –1,069 + 0,012 CD in mm + 0,001 NBW in grams -0,498 parity -0,057 maternal stature in cm -0,005 NS in mm. ROC analysis indicated that CD had better sensitivity and specificity than birthweight and neonatal ponderal index for prediction of FPD (p < 0,001). CONCLUSIONS.FPD occurred in 1,28% of pregnancies in a Lima hospital and was a serious obstetrical complication for both mother and infant’s health. Nulliparous women with stature less than 160 cm and fetuses with CD greater than 34 cm were at higher risk.